2016
DOI: 10.2355/isijinternational.isijint-2015-578
|View full text |Cite
|
Sign up to set email alerts
|

Improving Sintering Performance of Specularite Concentrates by Pre-briquetting Process

Abstract: With advantages of high Fe grade, less harmful impurities and relatively low price, specularite is one of ideal raw materials for improving sinter grade and reducing raw material cost. However its physicochemical characteristics lead to poor granulating performance and low degree of assimilation and melt generation at high temperature, consequently affect the productivity and quality of sinter. Unfortunately the existing methods of improving sintering performance for concentrates are not applicable to specular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…3.15 mm and -0.5 mm fractions of the reduced product sinter after tumbling, i.e., RDI ?6.3 mm , RDI ?3.15 mm and RDI -0.5 mm , respectively. Moreover, the maximum molecular and capillary water contents of limonitic nickel laterite were tested for the comparison with those of ordinary iron ores according to the literatures [21][22][23].…”
Section: Methodsmentioning
confidence: 99%
“…3.15 mm and -0.5 mm fractions of the reduced product sinter after tumbling, i.e., RDI ?6.3 mm , RDI ?3.15 mm and RDI -0.5 mm , respectively. Moreover, the maximum molecular and capillary water contents of limonitic nickel laterite were tested for the comparison with those of ordinary iron ores according to the literatures [21][22][23].…”
Section: Methodsmentioning
confidence: 99%
“…Then, the granules were loaded and sintered in a 180 mm diameter × 700 mm length sinter pot. The product sinter was tested for cold strength (tumble strength) according to ISO 3271-1995 [15], and then was crushed and sieved to 10-12.5 mm before reduction experiments. The chemical compositions of sinter samples were designed as follows: 56.08-57.02% Fe total , 5.7-6.0% SiO 2 , 10.3-10.8% CaO, basicity (CaO/SiO 2 ) 1.8, 1.33% Al 2 O 3 , 1.1% TiO 2 , and 1.36-3.10% MgO.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the suppression effect of increasing MgO content on reduction of sinter at low temperature could deservedly decrease the reducing innerstress and then improve the reduction degradation performance of sinter. In terms of the mechanism of suppression effect of MgO on reduction of sinter at low temperature, many relevant researches ascribed it to the changes in mineral composition, or rather in hematite quantity of sinter with increasing MgO content [11][12][13]15].…”
Section: Effect Of Mgo On the Reduction Degree And Reduction Rate Of Sinter At Low Temperaturementioning
confidence: 99%
“…(1) Previous work [2][3][4] demonstrated that an increase of concentrate in iron ore blend decreased the productivity of sinter. In this study a similar result was presented in the experiments with increases in the coarser commercial concentrates (mean size 0.1-0.3 mm).…”
Section: Discussionmentioning
confidence: 99%
“…However the productivity of sinter decreased with a decrease in the size of iron ore. 1) Many studies [2][3][4] demonstrated that an increase of concentrate in iron ore blend reduced the productivity in conventional sintering.…”
Section: Introductionmentioning
confidence: 99%